Teachers Knowledge, Attitude, and Awareness of Sustainable Development Education Among Urban Malaysian School - Abdullah, Abdul Ghani Kanesan; Ismail, Aziah binti (ANIMA Indonesian Psychological Journal, 2008)
This study aims to (a) identify the levels of knowledge, attitude, and awareness of teachers with regard to education for sustainable development; (b) identify the levels of knowledge about envi- ronmental education, (c) examine teaching methods to achieve sustainable development education, (d) examine the relationship of environmental education knowledge and sustainable education know- ledge, attitude, and awareness. Teachers (N = 104) were randomly selected from two northern states of Peninsular Malaysia to participate in this study. Data were collected through a questionnaire adapted from Clarke (1996). Results indicate 50% of the respondents did not understand nor have suf- ficient knowledge on education for sustainable development. Only 10 percent of the respondents were well versed with education for sustainable development compared to 40% of the respondents with moderate knowledge or understanding of the subject matter. Respondents preferred discussion, de- bate, and research projects to disseminate knowledge on environmental education. There is a signifi- cant (moderate) relationship between knowledge of environmental education and understanding (r = 0.583; p < 0.05); attitude (r = 0.531; p < 0.05); and awareness (r = 0.562; p < 0.05). Studi ini bertujuan (a) mengenali tingkat pengetahuan, sikap, dan kesadaran guru terkait pendidikan pengembangan berkesinambungan, (b) mengenali tingkat pengetahuan tentang pendidikan lingkungan, (c) menelaah metode pengajaran untuk mencapai pendidikan pengembangan berkesi- nambungan, (d) menelaah hubungan pengetahuan pendidikan lingkungan dan pengetahuan, sikap, dan kesadaran pendidikan berkesinambungan. Sejumlah guru (N = 104) dipilah secara acak dari dua nega- ra bagian di Utara semenanjung Malaysia untuk berpartisipasi dalam studi ini. Data diperoleh melalui hasil adaptasi kuesioner Clark (1996). Hasil menunjukkan bahwa 50% responden tidak mengerti dan tidak memiliki pengetahuan yang cukup tentang pendidikan pengembangan berkesinambungan. Hanya 10 % responden yang amat paham dibandingkan dengan 40% responden dengan pengetahuan yang cukup atau mengerti tentang masalahnya. Para responden lebih memilih diskusi, debat, dan proyek penelitian untuk menyebarkan pengetahuan tentang pendidikan lingkungan. Terdapat hubungan yang bermakna antara pengetahuan pendidikan lingkungan dan pengertian (r = 0.583; p < 0.05), sikap (r = 0.531, p < 0.05), dan kesadaran (r = 0.562; p < 0.05).